Association between bike-sharing systems and the blood pressure of local citizens: a cross-sectional study in China - Bing Li; Sumit Agarwal; Yuan Ren; Wenlan Qian; Rongju Sun (BMJ Publishing Group, 2024)
Introduction Globally, hypertension stands as the foremost preventable risk factor for cardiovascular disease and premature death. However, scalable approach to lowering blood pressure (BP) at the population level remains lacking. We investigated whether shared bikes, a sustainable method of transportation gaining increasing popularity across the world, can serve as a supplemental instrument to combat the increasing prevalence of hypertension.Methods Based on 8 107 363 physical examination visits to one of the largest medical examination centres in China during the period of June 2016 to August 2017, we perfermed a staggered difference-in-differences (DiD) analysis that exploited the roll-out of bike-sharing systems across different cities. The main outcome was the blood pressure among adult participants who were likely to adopt shared bikes (age <45), measured by (1) systolic blood pressure (SBP), (2) diastolic blood pressure (DBP) and (3) a binary indicator of hypertension status (SBP≥130 or DBP≥80 mm Hg).Results Blood pressure showed a decreasing trend after a bike-sharing platform entered the local city. After 6 months post an entry event, SBP reduced by 0.67 mm Hg (β (SE), −0.672 (0.245); 95% CI, −1.154 to −0.191); the prevalence of hypertension reduced by 1.4 percentage points (β (SE), −0.014 (0.007); 95% CI, −0.027 to −0.000); the reduction in DBP was statistically insignificant (β (SE), −0.193 (0.193); 95% CI, −0.572 to 0.187). Participants less likely to adopt shared bikes (age ≥45) showed no significant response. The number of visits and the age of participants were also unaffected by the entry events. Reduction in blood pressure was more pronounced in male, younger and non-obese participants.Conclusion The findings of this study suggest that bike-sharing systems in China may be associated with lowered blood pressure, and thus may serve as a supplemental instrument to combat the increasing prevalence of hypertension, especially among young adults.